論錢穆對漢代『春秋』學的硏究 - 楊兆貴; Yang¸ Zhao Gui; 趙殷尙; Cho¸ Eun Sang (중국학보, 2021)
錢穆對秦漢史、漢代經學研究飮譽學林, 影響很大。他這兩方面的論著大多已逾半世紀, 在出土文獻日益增多、研究方法多元化等學風下, 他的論著有哪些價值？對當代相關研究有什麼影響？筆者結合他這兩方面的研究, 聚焦他的漢代『春秋』學, 以見他治學、見解之一斑。 要探討他對漢代『春秋』學的看法, 則先簡介他對『春秋』及三傳的看法。他與傳統主張孔子作『春秋』的看法相同, 並從史學肯定『春秋』、『左傳』的史學價值。他認為漢代經學今古文之別是王官學與百家言之殊, 而非文字古今之異。這是他論漢代經今古文最具特色的部分。他撰『孔子與春秋』一文, 著重闡釋『公羊』學的精神, 強調孔子『春秋』以百家言而成為新的王官學。他在不同時期對『公羊』學與董仲舒的評價不同。他認為漢儒多通古今, 因此治『春秋』者多能兼採三傳或兩傳之義、說。他又指出, 『春秋』學與漢代思想尤其是災異說、禪讓說、禮制說有密切的關係。 Prof. Qian Mu has a great influence on the honorary scholars of Qin and Han history and Han dynasty studies. Most of his works in these two areas have been over half a century. With the increasing number of unearthed documents and diversified research methods, what is the value of his works? And what is the impact on contemporary related research? This essay combines his research in these two areas and focuses on his study of Chun Qiu in the Han Dynasty, so as to see his academic research methods and insights. To explore his views on the study of Chun Qiu in the Han Dynasty, the first part of the essay introduces his views on Chun Qiu and the three ‘Zhuan’. He is the same as the traditional view that Confucius wrote Chun Qiu, and affirmed the historical value of Chun Qiu and Zuo Zhuan from his historiography. He believes that the difference between modern and ancient literatures in Han dynasty is the difference between Ancient Official Document and Philosophers, rather than the difference between ancient and modern writing. He wrote the article Confucius and Chun Qiu, focusing on explaining the spirit of school of Gong Yang, emphasizing that Confucius' Chun Qiu became a new official ideology with the philosophical thought in Han China. He had different evaluations of Gong Yang and Dong Zhongshu in different periods. He believes that the Han scholars are mostly integrated with the ancient and modern literatures, so most of them who studied Chun Qiu can adopt the meaning and theories of the three or two ‘Zhuan’ at the same time. He also pointed out that the study of Chun Qiu has a close relationship with the thoughts of the Han Dynasty, especially the theory of catastrophe, concession, and etiquette.